(untitled) (Economic and Political Thought, 2020)
The article aims to analyse the impact of the government support programme “Family 500+” on the socioeconomic situation in Poland. The programme has been operating since April 2016, and it consists in the provision of monthly benefits to parents bringing up children. The benefit is granted for every child under the age of 18. The programme is supposed to reverse the drop in the number of births observed for many years as well as to improve the living conditions of the poorest families, and, in particular, to eliminate the phenomenon of extreme poverty. However, statistical data show that despite ambitious assumptions, the programme has not contributed to the improvement of the demographic situation of the country and the financial situation of families.